2014
DOI: 10.1038/hr.2014.116
|View full text |Cite
|
Sign up to set email alerts
|

Serial assessment of arterial stiffness by cardio-ankle vascular index for prediction of future cardiovascular events in patients with coronary artery disease

Abstract: Arterial stiffness is a significant predictor of cardiovascular disease (CVD), the risk of which is modified by medications for atherosclerotic risk factors and life-style changes. Cardio-ankle vascular index (CAVI) provides noninvasive, objective information on arterial stiffness, independent of blood pressure. This study aimed to investigate changes in CAVI after management of atherosclerotic risk factors, and the impact of these changes on future CVD outcomes in patients with coronary artery disease (CAD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 28 publications
2
54
0
7
Order By: Relevance
“…Furthermore, Otsuka et al 57) reported that persistently impaired CAVI was an independent predictor of future cardiovascular events (p 0.01), and cardiovascular outcomes were worse in patients with persistently impaired CAVI than in those with improved CAVI (p 0.001). This report suggests that the change in CAVI is also a predictor of future cardiovascular events.…”
Section: (C) Dyslipidemiamentioning
confidence: 99%
“…Furthermore, Otsuka et al 57) reported that persistently impaired CAVI was an independent predictor of future cardiovascular events (p 0.01), and cardiovascular outcomes were worse in patients with persistently impaired CAVI than in those with improved CAVI (p 0.001). This report suggests that the change in CAVI is also a predictor of future cardiovascular events.…”
Section: (C) Dyslipidemiamentioning
confidence: 99%
“…These results need to be detailed in a further study. Otsuka et al [76] reported that persistently impaired CAVI was an independent predictor of future cardiovascular disease events.…”
Section: Cavi As a Predictor Of Cardiovascular Eventsmentioning
confidence: 99%
“…The clinical importance of CAVI has been shown in various ethnic populations [22,23] and in disease conditions including hypertension [24], diabetes [25], coronary disease [26], and stroke [27]. A specific feature of the CAVI metric is its nondependence on BP changes during the time of measurement [9,10].…”
Section: Discussionmentioning
confidence: 99%